SOCIAL CONFLICT IN MSME COMPETITION: ANALYSIS USING SOCIAL CONFLICT THEORY - Ridiani Fitri; Arfriani Maifizar (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2026)
This study analyzes the phenomenon of social conflicts that arise due to fierce competition among Micro, Small, and Medium Enterprises (MSMEs), especially in the rapidly growing culinary sector in the digital era. Competition for limited resources, such as market share, raw materials, and access to capital, often triggers tensions and conflicts between business actors. Using a qualitative approach with a descriptive approach, data is collected through relevant journals. This analysis is based on  the Theory of Conflict by Karl Marx, which highlights class struggles and power inequality, and Lewis Coser, who sees conflict as a functional process that can strengthen group solidarity. The results of the study show that conflict manifests itself in various forms, ranging from unfair price competition to the spread of negative rumors. Conflict theory helps explain how resource imbalances perpetuate tensions, but also shows that constructive conflict management can encourage innovation and new collaboration among MSME actors.